Peran Neuro-Linguistic Programming dalam Pendidikan Islam: Analisis Sistematis Penguatan Karakter dan Pengembangan Sumber Daya Manusia - Irwan Suryadi; Rachmi Rachmi; Ahmadi Ahmadi (Idaarotul Ulum, 2025)
Islamic education plays a strategic role in shaping students’ character and developing human resources who are faithful, ethical, and competent. A major challenge is strengthening educators’ character and professionalism amid social dynamics and the complexities of modern human needs. This study examines the role of Neuro-Linguistic Programming (NLP) in Islamic education as a strategic approach for character building and human resource development. A qualitative approach using Library Research within a Systematic Literature Review (SLR) framework was employed, analyzing 34 relevant journals, books, and scientific proceedings. The findings show that NLP enhances self-awareness, emotional regulation, motivation, and effective communication, reinforcing positive character and behavior among students. Moreover, NLP supports educators’ professionalism and promotes value-based leadership and human resource management in Islamic educational institutions. Integrating NLP with ethical and prophetic leadership principles can sustainably improve human resource quality. The study concludes that NLP serves as a complementary, adaptive, and humanistic approach aligned with Islamic education goals, offering theoretical, practical, and policy implications for managing Islamic educational institutions.